Perancangan Arsitektur Interior Butik La Signature De Felicia dengan Konsep Tradisional Modern di Semarang - Nugroho, Felicia Yoanita; Utomo, Tri Noviyanto; Susan, Maria Yohana (Aksen : Journal of Design and Creative Industry, 2015)
Fashion becomes more important nowadays so that most women willing to spend their money in order to maintain their appearance. For that reason, most women like shopping especially fashion products. Women’s needs and desires to shop fashion products make a good opportunity to open a fashion business. Nowadays, many Indonesian people interested in batik clothing since the enactment of the 2nd of October as a national batik day, however many batik clothing models are outdated that makes teenagers and young adults not interested. Therefore modern batik clothing is the right choice for modern teenage girls and young adults because more varieties in patterns, colors, and models. La Signature De Felicia offers exclusive modern batik clothing ready-to-wear suitable for women. Based on modern batik products which are containing the traditional and modern, thus become the interior concept for La Signature De Felicia. The interior concept is ‘Transition’ which in interior means a blend of traditional and modern that uses traditional element umpak (base of a column in traditional Javanese house) which has been simplified so it looks more modern. Minimum of ornamentations and decorations keep the focus on the simplicity of the design. The colors are used the neutrals and warm tones to evoke clean look and as neutrals background colors for the products. This interior design is created to provide comfort for both customers and employees.